NanoLuc Luciferase – A Multifunctional Tool for High Throughput Antibody Screening - Boute, Nicolas; Lowe, Peter; Berger, Sven; Malissard, Martine; Robert, Alain; Tesar, Michael (Frontiers in Pharmacology, 2016)
Based on the recent development of NanoLuc Luciferase a small (19 kDa), highly stable, ATP independent, bioluminescent protein, an extremely robust and ultra high sensitivity screening system has been developed whereby primary hits of therapeutic antibodies and antibody fragments could be characterized and quantified without purification. This system is very versatile allowing cellular and solid phase ELISA but also homogeneous BRET based screening assays, relative affinity determinations with competition ELISA and direct western blotting. The new NanoLuc Luciferase protein fusion represents a “swiss army knife solution” for today and future high throughput antibody drug screenings.